Recycling edible vegetable oils by using various types of alkali with alcohol to produce biodiesel and study its optical and physical properties - Elbadawi, AA; Suliman, SA; Elkhair, HM; Abuelhassan, HH; Sabahelkhier, MK (International Journal of Environment, 2014)
In the present study, recycling edible oils which have been used in frying purposes of taamia, fish, potatoes, etc. are used to produce biodiesel in order to help in solving the fuel shortages and to share in the energy conservation efforts. Four types of biodiesels were prepared by treated the waste edible oil, firstly NaOH with methanol, secondly NaOH with ethanol, thirdly KOH with methanol, and fourthly KOH with ethanol. One liter of the cheapest and available used vegetable oils, 4gm of Alkali and 250ml of Alcohol was used for producing biodiesel. Optical tests for their absorption, density, viscosity and refractive index of the four produced biodiesels were compared with the fossil diesel (control biodiesel). The findings were showed that the properties of the prepared biodiesel samples are similar to the fossil diesel. DOI: http://dx.doi.org/10.3126/ije.v3i2.10525 International Journal of the Environment Vol.3(2) 2014: 143-149